2019
DOI: 10.3168/jds.2018-15219
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced supply of methionine or arginine alters mechanistic target of rapamycin signaling proteins, messenger RNA, and microRNA abundance in heat-stressed bovine mammary epithelial cells in vitro

Abstract: protein HSPA1A, the apoptotic gene BAX, and the translation inhibitor EIF4EBP1, the mRNA abundance of PPARG, FASN, ACACA (lipogenesis), and BCL2L1 (antiapoptotic) decreased. Greater supply of Met or Arg reversed most of the effects of HS occurring at the mRNA level and upregulated the abundance of HSPA1A. In addition, compared with the control, supply of Met or Arg upregulated genes related to transcription and translation (MAPK1, MTOR, SREBF1, RPS6KB1, JAK2), insulin signaling (AKT2, IRS1), AA transport (SLC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 52 publications
4
46
2
Order By: Relevance
“…Its role is to protect the cell and bind proteins to prevent their aggregation, and it has an antiapoptotic function [ 55 ]. In agreement with the results of the present study, Salama et al [ 56 ] and Hu et al [ 14 ] observed an increase in HSPA1A gene expression and the mRNA abundance of Hsp70 in mammary cells incubated at 42 °C in comparison with cells incubated at 36/38 °C. Considering other genes involved in apoptosis, heat stress increased the expression of BCL2, which is an antiapoptotic gene.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Its role is to protect the cell and bind proteins to prevent their aggregation, and it has an antiapoptotic function [ 55 ]. In agreement with the results of the present study, Salama et al [ 56 ] and Hu et al [ 14 ] observed an increase in HSPA1A gene expression and the mRNA abundance of Hsp70 in mammary cells incubated at 42 °C in comparison with cells incubated at 36/38 °C. Considering other genes involved in apoptosis, heat stress increased the expression of BCL2, which is an antiapoptotic gene.…”
Section: Resultssupporting
confidence: 93%
“…Kaufman et al [ 58 ] observed that heat stress reduced MTOR signaling pathway activity in mammary cells in vitro. Conversely, Salama et al [ 56 ] failed to find an effect of heat stress on the mRNA abundance of MTOR in bovine mammary cells in vitro. On the other hand, Chou et al [ 59 ] observed that MTOR has a key role in the synthesis of Hsp; in particular, a reduction in MTOR is accompanied by a reduction in the synthesis of Hsp70; in this way, cells become more sensitive to heat shock.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the levels of Met and Arg used in the present study were in accordance with our previous work. 16,17 Within those in vitro studies, although there was an overall positive effect on mammary cell metabolism, the negative effects on phosphorylation of 4E binding protein 1 (EIF4EBP1), eukaryotic elongation factor 2 (EEF2), 16 mTOR, 17 and mRNA abundance of β-casein and AA transporters 17 were partly consistent with the present results. Similarly, despite using EAA profiles similar to those in IPAA, previous in vivo studies also reported results contrary to ours, for instance phosphorylation ratio of ribosomal protein S6 (RPS6) was lower at a Lys : Met = 2.9 : 1 41 and milk protein synthesis or the efficiency of N utilization was not modified at an Lys : Arg = 2 : 1.…”
Section: Food and Function Papersupporting
confidence: 90%
“…Recent in vitro studies reported a positive effect of greater Arg supply (Lys : Arg at 1 : 1) on mRNA and protein abundance of various components of the milk protein synthesis network, 16 but a negative impact of supplying Met beyond the 3 : 1 ratio of Lys : Met. 17 Although most published studies have focused on the optimal supply of Met and Arg with respect to the role of mTORC1 downstream factors on milk protein synthesis, recent research has identified important roles of factors upstream of mTORC1, 18,19 AA transporters 20 and AA sensors 21,22 in the overall regulation of protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…After being activated, the mTOR pathway regulates its targets to promote milk protein synthesis [ 65 ]. It has been reported that bovine mammary cells, which were incubated in high temperature (42 °C), reduced protein translation by reducing the mTOR downstream pathway activity [ 66 , 67 ]. In contrast to the findings of Kaufman et al [ 66 ] and Salama et al [ 67 ], we observed that heat exposure to cows enhanced the gene expression of CASTOR1 , CASTOR2 and phosphorylation of mTOR.…”
Section: Discussionmentioning
confidence: 99%